Temporal Trends in Cervical Cancer Screening Practices and Associated Downstream Abnormalities and Procedures Among Women With Insurance in the United States. Issue 1 (7th July 2022) - Liao, Lillian; Chen, Ling; Gockley, Allison; Melamed, Alexander; St Clair, Caryn M.; Hou, June Y.; Khoury-Collado, Fady; Accordino, Melissa; Hershman, Dawn L.; Wright, Jason D.
Abstract : Incorporation of human papillomavirus testing into cervical cancer screening is associated with an increased trend in downstream abnormalities and procedures among screened women but a declining trend at the population level. Abstract : OBJECTIVE: To examine temporal trends in cervical cancer screening practices and associated downstream abnormalities and procedures. METHODS: Women aged 18–64 years with commercial insurance or Medicaid insurance from 2008 to 2019 were identified using the IBM MarketScan databases. The annual rates of screening overall and by type of test (cytology, co-testing, or primary human papillomavirus testing) were examined. Downstream abnormal cytologic and histologic test results, colposcopies, and excisional procedures were examined, and rates were reported for the population of eligible patients with continuous insurance and for those who underwent screening. Changes over time in testing and outcomes were compared using χ 2 tests and Spearman's correlation. RESULTS: From 2008 to 2019, the annual screening prevalence decreased from 42.6% to 29.4% in women with commercial insurance ( P <.001) and from 27.9% to 12.4% among women with Medicaid insurance ( P <.001). In the cohort of women with commercial insurance, cytology usage decreased from 79.4% to 38.9% and co-testing increased from 20.1% to 59.6% ( P <.001). Per 1, 000 women screened, the rate of abnormal histologic and cytologic test results rose from 96 to 119 ( P <.001) and colposcopies rose from 33 to 42 ( P <.001); excisional procedures remained relatively constant. Per 1, 000 eligible women, the rate of abnormal histologic and cytologic test results decreased from 41 to 35 ( P <.001), colposcopies declined from 14 to 12, and excisional procedures decreased from 3 to 2. CONCLUSION: Human papillomavirus testing has been rapidly incorporated into cervical cancer screening and is associated with an increasing trend of downstream abnormalities and procedures among screened women but a declining trend at the population level.